Transcatheter closure of paravalvular leaks using a paravalvular leak device – a prospective Polish registry - Smolka, Grzegorz; Pysz, Piotr; Kozłowski, Michał; Jasiński, Marek; Gocoł, Radosław; Roleder, Tomasz; Kargul, Agnieszka; Ochała, Andrzej; Wojakowski, Wojciech (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Transcatheter paravalvular leak closure (TPVLC) has become an established treatment option but is mostly performed with off-label use of different non-dedicated occluders. The first one specifically designed for TPVLC is the paravalvular leak device (PLD – Occlutech). Aim : We present initial short-term results of a prospective registry intended to assess the safety and efficacy of TPVLC with PLD. Material and methods : We screened patients with paravalvular leak (PVL) after surgical valve replacement (SVR). Heart failure symptoms and/or hemolytic anemia were indications for TPVLC. Patients were selected according to PVL anatomy by RT 3D TEE. Only those considered appropriate for closure with a single PLD were enrolled. The procedures were performed via transvascular or transapical access using type W (waist) PLDs only. Results : Thirty patients with 34 PVLs (18 aortic, 16 mitral) were included. We implanted 35 PLDs with a total device success rate of 94.3% (100% for aortic, 88.2% for mitral). The procedural success rate, encompassing device success without in-hospital complications, was 94.1% (100% for aortic, 93.8% for mitral). During the follow-up period we recorded an increase of hemoglobin concentration (3.9 to 4.1 g/dl), red blood count (11.6 to 12.2 M/mm3) and functional improvement by NYHA class. Conclusions : Paravalvular leak device type W is a promising TPVLC device, but meticulous preselection of patients based on imaging of PVL anatomy is a prerequisite. A PLD should only be chosen for channels shorter than 5 mm. Size of the device should match the PVL cross-sectional area without any oversizing. Such an approach facilitates high device and procedural success rates.